Etnologi sebagai Instrumen Perilaku Ekonomi dalam Perspektif Alquran: Indonesia - Ahmad, Upi Sopiah (Mubeza, 2022)
Islam entered Indonesia, and even Southeast Asia through traders who carried out economic activities (trade) and preached. Based on the Qur'an, economic activities or behavior are carried out according to the principles of the Qur'an consistently by utilizing the available resources to increase the added value of the product and to gain the pleasure of Allah. Economic behavior is also influenced by the values attached to an economic community. Economic activity is part of work, in an economic perspective, work is an effort made by a person to meet physical and spiritual needs. Individuals who develop their creativity based on values (revelation) in the reality of life in accordance with the Qur'an will produce a culture that is in accordance with the Qur'an, and vice versa, individuals who develop their creativity contrary to the values of the Qur'an will produce a culture that is non-Qur'anic or not in accordance with the Qur'an. Ideas or ideas contained in a community group will form certain patterns in the economy. Entrepreneurship is rooted in the socio-cultural, political and economic context in which people learn to carry out their functions. Ethnology explores and empowers local wisdom. Culture that is based on Islamic, faith, and human creativity will produce a quranic culture. The compatibility of cultural values with the Qur'an is the main instrument in shaping economic behavior in accordance with Islamic values, so that culture or ethnology becomes important as an instrument in shaping the economic behavior of the community